2022
DOI: 10.1096/fasebj.2022.36.s1.r2236
|View full text |Cite
|
Sign up to set email alerts
|

High‐Density Lipoprotein is Independently Associated with Muscle Mitochondrial Function in Healthy Humans

Abstract: High‐density lipoprotein cholesterol (HDL‐C) is well known to play an important anti‐atherogenic role via reverse cholesterol transport. Increasing number of studies in mice have also suggested a protective role of HDL in preserving muscle mitochondrial function via ApoA1‐induced enhancement of cellular respiration of glucose. However, data in humans are lacking. We therefore hypothesize that HDL levels and/or function are correlated with muscle mitochondrial function in humans. Accordingly, we conducted a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Conversely, inverse relationships between HDL-C and central obesity were discovered [29], and elevated intra-abdominal pressure brought on by high levels of central obesity, insulin resistance, and oxidative stress leading to pelvic floor vascular injury with sphincter and forced urinary muscle dysfunction are some of the potential mechanisms that may cause UI [30]. It has been observed that in healthy young to middle-aged individuals without cardiometabolic disease, HDL-C and apolipoprotein A-I improve skeletal muscle [31]. Low HDL-C levels are linked to SUI, which may be explained by the correlation between trunk muscle mass and the status and severity of SUI [32].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inverse relationships between HDL-C and central obesity were discovered [29], and elevated intra-abdominal pressure brought on by high levels of central obesity, insulin resistance, and oxidative stress leading to pelvic floor vascular injury with sphincter and forced urinary muscle dysfunction are some of the potential mechanisms that may cause UI [30]. It has been observed that in healthy young to middle-aged individuals without cardiometabolic disease, HDL-C and apolipoprotein A-I improve skeletal muscle [31]. Low HDL-C levels are linked to SUI, which may be explained by the correlation between trunk muscle mass and the status and severity of SUI [32].…”
Section: Discussionmentioning
confidence: 99%